Drag reducing polymers attenuate adverse effects of ischemia-reperfusion upon resection of liver metastases modeled by MC38 mouse colon adenocarcinomama - Burlaka, А.А.; Burlaka, А.P.; Кrotevych, М.S.; Rudiuk, Т.О.; Orel, V.E. (PH Akademperiodyka, 2023)
Summary. Background: The resection of metastases within healthy parenchyma improves significantly the long-term outcome in metastatic colorectal cancer. Until now, the resection technique involves Pringle maneuver, which allows reducing blood loss during transsection of liver parenchyma. However, the classical Pringle maneuver has restrictions due to ischemia/reperfusion (I/R) effect, in particular increasing risk of tumor recurrence after liver surgery. Aim: To study the pathological impact of surgical intervention and I/R effect on healthy liver tissue in the experimental setting by evaluating the markers of redox-homeostasis and oxidatively induced mutagenesis, and also to assess the current possibilities of their correction by application of drag-reducing polymers (DRPs). Materials and Methods: MC38 mouse colon adenocarcinoma cells were transplanted intrahepatically to C57Bl/6 mice. The influence of warm ischemia on metastatic potential of MC38 cells, the speed of superoxide radicals (SR) generation and 8-hydroxydeoxyguanosine content were studied. Results: In case of modeled liver metastases, the surgery initiates an increase in the rate of SR generation into the remaining liver tissue and, consequently, provokes its ischemic injury. The application of DRPs protects liver tissue under I/R conditions. Conclusions: The warm I/R can promotes metastatic lesions in the healthy part of the organ with underlying increase in the rate of SR generation and oxidatively induced damage of guanine in DNA. The hemorheological effects of DRPs ensure increase of microcirculatory perfusion and oxygenation of liver tissues with the reduction of the rate of SR generation and decrease of 8-hydroxydeoxyguanosine as a marker of oxidatively induced mutations in DNA of hepatocytes. The intraperitoneal administration of nanomolar doses of DRPs prevents the activation of the growth of dormant metastatic MC38 cells in the liver. Further experimental and clinical study of these substances will allow reducing the risks of activation of uncontrolled tumor growth in the liver due to the pathological effect of post-operative I/R.